Photocatalytic degradation of methyl orange using Carbon Quantum Dots (CQDs) derived from watermelon rinds - U. R. R. P., Remli; Azrina, Abd Aziz (IOP Publishing, 2020)
In this study, a facile synthesis of carbon quantum dots (CQDs) was successfully conducted by hydrothermal treatment at mild temperature (120 °C) using watermelon rinds as carbon precursor. The synthesized CQDs was aimed to harvest the visible light from artificial source for photocatalytic degradation of methyl orange (MO) dye. The prepared CQDs were characterized by TEM to check the physical properties. The produced CQDs demonstrated a band of spherical dots which display a complete dispersion of particles in water. The spherical morphology of the CQDs was clearly seen with narrow size distribution, averagely around 1 -5 nm in diameter. The CQDs exhibited an excellent photocatalytic performance with 68.9% of MO degradation rate within 120 min reaction owing to the large surface area for adsorption and reaction process to take place.